2004
DOI: 10.1073/pnas.0400848101
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of age-related changes of physiological processes that predict lifespan of Caenorhabditis elegans

Abstract: Aging is characterized by progressive, degenerative changes in many tissues. To elucidate the relationships among degenerative changes in Caenorhabditis elegans, we developed methods to measure age-related changes quantitatively and analyzed correlations among these changes by using a longitudinal study. The age-related declines of pharyngeal pumping and body movement were positively correlated with each other and lifespan. These findings suggest that the declines of pharyngeal pumping and body movement cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
547
4
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 481 publications
(607 citation statements)
references
References 35 publications
(48 reference statements)
45
547
4
1
Order By: Relevance
“…Diminishing movement as a function of age has been documented in multiple studies (Bolanowski, Russell, & Jacobson, 1981; Glenn et al., 2004; Herndon et al., 2002; Huang, Xiong, & Kornfeld, 2004; Johnson, 1987). Here, we use a method similar to that of Hosono, Sato, Aizawa, and Mitsui (1980) and Herndon et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diminishing movement as a function of age has been documented in multiple studies (Bolanowski, Russell, & Jacobson, 1981; Glenn et al., 2004; Herndon et al., 2002; Huang, Xiong, & Kornfeld, 2004; Johnson, 1987). Here, we use a method similar to that of Hosono, Sato, Aizawa, and Mitsui (1980) and Herndon et al.…”
Section: Resultsmentioning
confidence: 99%
“…Retention of Class A movement has been used as a marker of extended healthspan (Herndon et al., 2002; Huang et al., 2004). We observed that long‐lived mutants generally retain Class A behavior longer (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2004), except that the N2 worms used were selected at random from the populations within the lifespan assay. For the movement assay, the plates were firmly tapped onto the microscope to stimulate movement.…”
Section: Methodsmentioning
confidence: 99%
“…While cause and effect cannot be directly inferred from these data, the correlation between pharyngeal pumping rescue and lifespan extension is striking and warrants further investigation. Previous studies indicated that a reduced rate of pharyngeal pumping was highly correlated to organismal aging in C. elegans (Huang et al, 2004). Pumping rates decrease with age in wild-type animals and mutations that affect lifespan concomitantly affect pumping rates (Huang et al, 2004).…”
Section: Fig 5 Expression Of Nfi-1-gfp From the Myo-3 Promoter Indumentioning
confidence: 99%